Hubungan Perubahan Penggunaan Lahan dengan Limpasan Air Permukiman: Studi Kasus Kota Bogor - Nia Kurniasih Pontoh (The Institute for Research and Community Services, Institut Teknologi Bandung, 2005)
Bogor City is one of cities function ing as counter magnet forJakarta, the capital city of Indonesia . There is a rapid land use change in Bogor that reduce the capacity to absorp water and increase the surface run -off water. Knowing that the position City of Bogor is located in center part of Ciliwung riverbasin and giving significant contribution to increasing the rate of flow o f river water. Run-off controlling is very important to decrease the flood threat for Jakarta and to increase the composit e of land water for City of Bogor itself. The study uses shift -share method analyzes comparing types and area of land use in different time . The result of study describe that the change of land -use will be influenced much by the condition of environment.Keywords: land-use change, run-off water, flood threat